Manufacturing Strategy and New Venture Performance: A Comparison of Independent and Corporate Ventures in the Biotechnology Industry - ZAHRA, Shaker A. (Institutional Knowledge at Singapore Management University, 1999)
Little empirical research has compared the manufacturing strategies of corporate and independent new ventures. This study explores these differences with data from the young, science-based biotechnology industry, and examines the performance effects of manufacturing strategy variables including scope, competitive thrust, and capabilities. The results show that the corporate and independent biotechnology new ventures pursue significantly different manufacturing strategies, and that different dimensions of manufacturing strategies affect the performance of corporate vs. independent ventures quite differently.